Role of apoptosis in gastric epithelial turnover - Herbay, Axel von; Rudi, Jochen (Microscopy research and technique, 2000)
Gastric epithelial turnover is a dynamic process. It is characterized by continous cell proliferation, which is counterbalanced by cell loss. The biological principle that mediates the homeostasis of epithelium is programmed cell death, or apoptosis. Currently, several subtypes of apoptosis are distinguished, which are mediated by different mechanisms. Various subtypes of apoptosis also occur in the gastric epithelium under various conditions.